Teaching of Science in Upper Primary Special Training Centers for Out-of School Children - Mohla, R.M. (SCHOOL SCIENCE, 2017)
Delhi State Science Teachers’ Forum (DSSTF) is an organisation of science teachers of different management schools of Delhi. DSSTF was conceptualised and visualised with the objective of inculcating scientific attitude, scientific temper in teachers and students, to popularise science subject in schools by bringing quality of teaching science with the help of hands-on activities/science kits, free science teaching camps (for SC/ST and economically backward students) and conducting workshops, seminars, exhibition and celebration of National Science Day and birth days of eminent scientists. For improving and increasing the popularity of science subject in schools of Delhi, science open merit test is introduced by DSSTF in Class X, so that the quality crop of science students could be created to benefit students of Delhi. Among other activities of DSSTF special mention is to be made of training of lab assistants, training of science teachers, preparing manual and material for science teachers teaching at elementary and secondary levels. The main activity of DSSTF is free science teaching camps (for SC/ST and economically backward students) for elementary and secondary classes. The main feature of these camps which are running in government schools of Delhi since 1989 is that more than thousand science teachers, who are life members of the forum, are teaching in these camps voluntarily. These camps are arranged during autumn and winter breaks. All science teachers who offer to teach in these camps are given subjects of their priority including physics, chemistry and biology stream. The topics are assigned to DSSTF members as per their specific interest in theory and practical at the elementary and secondary levels. These teachers are trained for performing practical and scientific activities related to their topics by experts of DSSTF. In the year 2016, DSSTF has launched a new innovative project of science for upper primary students of STCs running in schools of Delhi by SSA to whom even fundamentals of science are not known. These STCs are run by SSA Delhi funded by MHRD, Government of India. The State Project Director of SSA and RMSA was approached by functionaries of DSSTF. The DSSTF members offered to teach science in these STCs all over Delhi and the kits provided by SSA Delhi was made available to these science teachers by State Project Director, SSA. This paper presents a successful intervention and our experience of science teaching with groups of out-of-school children in three government schools of Delhi.